(untitled) (Journal of Food and Dietetics Research, 2024)
With increasing nutritional awareness among consumers, the value addition of snacks is gaining importance. The development and availability of value-added, nutridense snacks encourage consumers to make healthy snack choices. Value-added and nutridense snacks consumed by school-going children can contribute to a significant source of energy and nutrients. Lotus root is a less utilized vegetable containing various nutrients. It is a rich source of polyphenols, antioxidants, and dietary fiber. Lotus root is a versatile, culinary delicacy that can be cooked in different ways by stir-frying, boiling, braising, steaming, or deep-frying. This investigation was undertaken to develop a value-added, nutritious Nutribite Crackers, crispy textured and attractive lotus root-based snack for all age groups, especially pre-school and school children. Regular maize flour-based crackers were prepared and standardized as a control sample (MFC). Nutribite Crackers in three different variations (V-1, V-2, and V-3) were prepared using a combination of Lotus root, Maize flour, Wheat flour, Bajra flour, and Jowar flour. The developed crackers (Control: MFC and Variations: V-1, V-2, and V-3) were subjected to sensory evaluation, using a 9-point hedonic rating scale, to study the acceptability by 50 semi-trained panelists. Sensory evaluation results revealed that Nutribite Crackers prepared using Wheat flour, Maize flour, and Lotus root (V-1) were found to be most acceptable with total mean score of (52.02) out of (54), followed by (V-2) prepared using Jowar flour with a total mean score of (49.92) out of (54), then followed by (V-3) prepared using Bajra flour with total mean score of (47.84) out of (54). 100 g of best-rated Nutribite Crackers (V-1) has 545.85 kcal, 4.93 % crude protein, 20.37 % crude fat, 69.80 % carbohydrate, 1621.00 mg/kg potassium, 380.78 mg/kg calcium and 46.77 mg/kg iron. Control and all three variations showed a shelf life of more than 30 days under normal storage conditions. Lotus root incorporated Nutribite crackers (V-1) developed and standardized in this investigation serve as an ideal snack with several health-promoting nutrients for consumers.